Economic Vulnerability and Flood Risk: Evidence from the East Coast Households of Peninsular Malaysia - Hassan, sallahuddin (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this paper are to compare the discrepancies in economic vulnerability levels and evaluate the effects of economic vulnerability on flood risk among affected households in the East Coast states of Peninsular Malaysia By developing its component within a household flood vulnerability index (FVI) from a sample of 380 households and employing a multiple regression analysis, the findings vary by district, state and region. Among others, Kota Bharu and Temerloh are the two districts’ most economically vulnerable to floods with their highest economic FVI values of 0.736 and 0.631, respectively. Meanwhile, Pahang is the state’s most economically vulnerable to floods with the highest economic FVI value of 0.655. Also, key determinants; proximity to river, businesses, flood insurance holders and economic recovery may influence any change in flood risk among the households. Therefore, decision and policy makers are recommended to explore possible ways of optimizing the flood recovery process from pre-disaster community procedures such as code adoption policies and early recovery decisions via vertical and organizational integrations among households, communities, businesses, donor agencies, infrastructural providers and local governments.